The social contract: An analytical tool for countries in the Middle East and North Africa (MENA) and beyond - Markus Loewe; Bernhard Trautner; Tina Zintl (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
The social contract is a key concept in social science literature focusing on state-society relations. It refers to the "entirety of explicit or implicit agreements between all relevant societal groups and the sovereign (i.e. the government or any other actor in power), defining their rights and obligations towards each other" (Loewe & Zintl, forthcoming). The analysis of social contracts helps the understanding of: (i) why some societal groups are socially, politically or economically better off than others, (ii) why some revolt and demand a new social contract and, thus, (iii) why a country descends into violent conflict. In addition, the concept shows how foreign interventions and international co-operation may affect state-society relations by strengthening the position of the state or of specific societal groups. It illustrates that state fragility, displacement and migration can arise from social contracts becoming less inclusive. Nevertheless, the term "social contract" has so far been neither well defined nor operationalised - to the detriment of both research and of bi- and multilateral co-operation. Such a structured analytical approach to state-society relations is badly needed both in research and in politics, in particular but not exclusively for the analysis of MENA countries. This briefing paper sets the frame, suggesting a close analysis of (i) the scope of social contracts, (ii) their substance and (iii) their temporal dimension. After independence, MENA governments established a specific kind of social contract with citizens, mainly based on the redistribution of rents from natural resources, development aid and other forms of transfers. They provided subsidised food and energy, free public education and government jobs to citizens in compensation for the tacit recognition of political regimes' legitimacy despite a lack of political participation. But with growing populations and declining state revenues, some governments lost their ability to fulfil their duties and focused spending on strategically important social groups, increasingly tying resource provision to political acquiescence. The uprisings that took place in many Arab countries in 2011 can be seen as an expression of deep dissatisfaction with social contracts that no longer provided either political participation or substantial social benefits (at least for large parts of the population). After the uprisings, MENA countries developed in different directions. While Tunisia is a fair way towards more inclusive development and political participation, Morocco and Jordan are trying to restore some parts of the former social contract, providing for paternalistic distribution without substantial participation. In Egypt's emerging social contract, the government promises little more than individual and collective security, and that only under the condition of full political acquiescence. Libya, Yemen and Syria have fallen into civil wars with no countrywide new contract in sight, and Iraq has been struggling for one since 2003. In addition, flight and migration also affect the social contracts of neighbouring countries such as Jordan, Turkey, and Lebanon. All MENA countries are designing, or will need to design, new social contracts in order to reduce the current instability and enable physical reconstruction. This briefing paper informs on the status of conceptual considerations of social contract renegotiation in MENA countries and its meaning for international co-operation with them.
Keywords: 330